Pemanfaatan Teknologi Digital dalam Supervisi Pembelajaran Pendidikan Agama Islam - Frawina, Mutia; Iqbal, Muhammad (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to examine the utilization of digital technology in Islamic Religious Education (PAI) supervision, identify challenges emerging during its implementation, and formulate strategic solutions to ensure effective and sustainable digital supervision. Using a library research method, data were collected through the selection of relevant, up-to-date literature contributing to the theme of digital technology in educational supervision. The data sources for this study include scientific journal articles, academic books, and previous research findings, which were analyzed using a content analysis approach to identify key findings and emerging conceptual patterns. The results indicate that digital technology is utilized through web-based e-supervision platforms, academic supervision applications, digital collaboration tools, and integrated data management systems. However, constraints such as infrastructure limitations, low digital literacy, and data security issues remain the primary obstacles. Strategic solutions proposed include strengthening technological facilities, continuous digital competence training, developing supportive institutional policies, and implementing robust data protection systems.